2018
DOI: 10.1080/02699206.2018.1513075
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of disfluencies in typical, fast and cluttered speech

Abstract: Cluttering is a fluency disorder which can be characterised by excessive disfluencies. However, the low number of studies dealing with the analysis of disfluencies in cluttering show contradictory results. The aim of this article is to analyse disfluency clusters in cluttered, fast and typical speech. Frequency of all disfluency clusters and those complex disfluencies which contain more than two constituents were analysed. The number and types of the constituents of complex disfluencies and the reason of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(36 reference statements)
1
6
0
1
Order By: Relevance
“…Literature on these distributional issues is much more scarce, some few exceptions to be mentioned include e.g. [Crible et al 2017], [Betz et al 2015], [Betz and Kosmala 2019], [Bóna 2019]. Our paper is in line with this distributional approach, which we advocate and check against Russian data.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Literature on these distributional issues is much more scarce, some few exceptions to be mentioned include e.g. [Crible et al 2017], [Betz et al 2015], [Betz and Kosmala 2019], [Bóna 2019]. Our paper is in line with this distributional approach, which we advocate and check against Russian data.…”
Section: Introductionsupporting
confidence: 73%
“…Overall, five adjacent disfluency tokens precede a stretch of fluent speech. We consider the opposition of isolated vs. clustered disfluencies significant, as the latter type presumably indicates more severe difficulties than the former (see, e.g., [Robb et al 2009]; [Bóna 2019] for clinical accounts on clustering). However, there is no clear-cut between these two types.…”
Section: Isolated Vs Clustered Disfluenciesmentioning
confidence: 99%
“…Further, Garnett and St. Louis (2010) also reported twice as many disfluencies in PWC's speech than in the speech of typical speakers. Several studies, however, found no significant differences between PWC and typical speakers in the frequency of all disfluencies (Bakker et al, 2011;Myers et al, 2012;Bóna, 2016Bóna, , 2018. Contradictory results might emerge due to the small number of participants and large individual characteristics.…”
Section: Introductionmentioning
confidence: 92%
“…Existing studies of disfluency clusters are mostly based on data from children with developmental stuttering (LaSalle & Huffman, 2015;Sawyer & Yairi, 2010) and from adults with persistent stuttering (Robb et al, 2009) or cluttering (Bóna, 2018(Bóna, , 2019Myers et al, 2012Myers et al, , 2008. There are only a couple studies on disfluency clusters in typical adult speakers (Bóna, 2018(Bóna, , 2019Myers et al, 2012), and even rarer are studies on disfluency clusters in atypical speech without classical fluency disorders . Myers et al (2012) investigated disfluencies and disfluency clusters in fluent adults and in adults with developmental cluttering (PWC).…”
Section: Disfluency Clustersmentioning
confidence: 99%